ANALISIS PENDAPATAN PETERNAK ITIK PETELUR SISTEM PEMELIHARAAN NOMADEN DI DESA KALIANG, KECAMATAN DUAMPANUA, KABUPATEN PINRANG - Rohani, Nurana, St.; Kasim, Kasmiyati (Jurnal Ilmu dan Industri Peternakan, 2016)
ABSTRACT. Animal husbandry laying ducks is dominated breeder by maintenance system the that is still traditional where laying ducks shepherding in the paddy field or in the place many waters. Maintenance system that many applied by breeder ie system nomadic maintenance, breeder sometimes do not know how much income obtained from the business of laying ducks of system nomadic maintenance. Therefor the in developing businesses laying ducks which run, it is important to know how much revenue the breeder itself with system nomadic maintenance. The purpose of this study is to describe the nomadic maintenance system and the income of breeder laying ducks in the kaliang village, District Duampanua, Regency Pinrang. This study was implemented on months April to May 2014 and data retrieval is housed in the kaliang Village, District Duampanua, Regency Pinrang. This type of research used in this study was descriptive quantitative research is research that describes the type of the variable in which questionable without testing the hypothesis. Analysis of the data used are descriptive statistics. Results showed that System nomadic maintenance laying ducks in the kaliang Village, District Duampanua, regency Pinrang done with laying ducks grazing in the paddy field that already been harvested, later transferred to other areas when planting season arrives and revenue breeder laying ducks of system nomadic maintenance highest is Rp. 7.520.832 with the R/C ie 1,15% and a low of Rp. 1.703.144 ie the R/C is 1.07%. The difference in the income of breeder due to differences in the number of livestock laying ducks owned .